Knowing bodies, passionate souls: sense perception in Byzantium - Harvey, Susan Ashbrook; Mullett, Margaret (Dumbarton Oaks Byzantine symposia and colloquia, 2017)
"Byzantine culture was notably attuned to a cosmos of multiple dominions: material, bodily, intellectual, physical, spiritual, human, divine. Despite a prevailing discourse to the contrary, the Byzantine world found its bridges between domains most often in sensory modes of awareness. These different domains were concretely perceptible and were encountered daily amidst the mundane no less than the exalted. Icons, incense, music, sacred architecture, ritual activity; saints, imperial families, persons at prayer; hymnography, ascetical or mystical literature: in all of its cultural expressions, the Byzantines excelled in highlighting the intersections between human and divine realms through sensory engagement (whether positive or negative). Byzantinists have been slow to look at the operations of the senses in Byzantium, especially those of seeing, its relation to the other senses, and phenomenological approaches in general. More recently, work on smell and hearing has followed that on seeing, and yet the areas of taste and touch--the most universal and most necessary of the senses--are still largely uncharted. Nor has much been done to explore how Byzantines viewed the senses, or how they envisaged the sensory interactions with their world. A map of the connections between sense-perceptions and other processes (of perception, memory, visualization) in the Byzantine brain has still to be sketched out. How did the Byzantines describe, narrate, or represent the senses at work? It is hoped to further studies of how individual senses in Byzantium operated in the context of all the senses, and their place in Byzantine thought about perception and cognition. Recent work on dreaming, on memory, and on the emotions has made advances possible, and collaborative experiments between Byzantinists and neurological scientists open further approaches. The happy coincidence of this symposium with the upcoming Garden and Landscape Studies Symposium, 'Sound and Scent in the Garden,' and a forthcoming exhibition at the Walters Art Museum on the five senses enables cross-cultural comparisons that include gardens in Islamic Spain, Hebrew hymnography, Syriac wine-poetry, Mediterranean ordure, and Romanesque and Gothic precious objects that were not just looked at but also touched, smelled, and heard. Architects, musicologists, art historians, archaeologists, philologists can all contribute approaches to the revelation of the Byzantine sensorium"--From publisher's website